Adsorption of Methane in porous materials as the basis for the storage of Natural Gas - Solar, Cecilia (2010)
It is well known that the natural gas (NG) is a substance of fossil origin from the decomposition of organic matter. It is found trapped under the terrestrial surface in stratus that avoid the natural release to atmosphere. These underground deposits can be oceanic or terrestrial. The NG is a homogeneous mixture, having variable proportions of hydrocarbons, being the main constitute the methane (CH4), which content generally ranges from 55 to 98 % in volume. Also, it contains ethane (C2H6), propane (C3H8) and heavier constitutes. Although it can be found in gas phase or in solution with oil, under normal atmospheric conditions, remains in gas phase. It may have some impurities or substances that are not hydrocarbons, such as Hydrogen Sulfide, Nitrogen and Carbon Dioxide (Figure 1). According to its origin, natural gas is classified in associated and non-associated, being the first, the one which remains in contact and/or dissolved with the oil from the deposit. The non-associated gas can be found in deposits lacking oil crude at the initial conditions of pressure and temperature.